CORRELATION BETWEEN DIABETES MELLITUS AND THE INCIDENCE OF CATARACT AT DEPARTEMENT OF OPHTHALMOLOGY MATARAM UNIVERSITY HOSPITAL IN 2020 - Bella Insani Kamil (Faculty of Medicine Universitas Mataram, 2022)
Background: Cataract is the main reason of blindness in Indonesia which is 77.7% of blindness is caused by cataracts. It is known that there is an increase in the incidence of cataracts among patients with Diabetes Mellitus, and the possibility is 25 times higher than people without Diabetes Mellitus. Diabetes is a crucial public health problem due to the number of cases and the prevalence of diabetes have continued to increase over the last few decades. Diabetes and cataracts are considered has high impact in term of health and economic burden, especially for developing countries that do not yet have good diabetes management and difficult access to cataract surgery. The aim of this research was to know about the correlation between diabetes mellitus and the incidence of cataract. Methods: This is an analytic study using a cross sectional research design. The sampling technique used is total sampling. This study used secondary data which obtained from patient medical records at the departement of ophthalmology of Unram Hospital from January 2020 to December 2020 with a total number of patients was 34 people. Data was analyzed using the Chi Square test calculation method. Results: The result showed there was no significant relationship between diabetes mellitus and the incidence of cataracts (p > 0.05) Conclusion: There was no significant relationship between diabetes mellitus and the incidence of cataracts with the most cataract patients aged 60-69 years Keywords: Diabetes Mellitus, Senile Cataract, Mataram University Hospital